Resort architecture in Langkawi, Malaysia - 397413 Aymen Mohamed Elmagalfta author; Ahmad Sanusi Hassan author; Ku Azhar Ku Hassan author (Pulau Pinang : Penerbit Universiti Sains Malaysia, 2009)
Includes bibliographical references and index.